Structural Equation Modeling for Successful Water Management in the Northeastern Mekong River Basin under the Royal Irrigation Department - Panyaprachum, Parichat; Tantrabundit, Pongsatorn (Engineering Access, 2026)
This study aims to: (1) examine the influence of causal factors that affect the success of water management, and (2) verify the consistency of the developed model with empirical data. This is a quantitative research study that employed questionnaires distributed to 375 staff members responsible for water management under the Royal Irrigation Department in the Northeastern Mekong River Basin. The participants were from 15 agencies and had at least one year of work experience. The data were analyzed using Structural Equation Modeling (SEM) techniques. The findings from the quantitative research were also analyzed qualitatively using the documentary analysis method. The results revealed that: (1) Continuous quality improvement, becoming a learning organization, leadership, farmer participation, and environmental conditions all had a statistically significant influence (at the 0.05 level) on the success of water management by the Royal Irrigation Department, with influence values of 0.93, 0.90, 0.80, and 0.71, respectively. Therefore, a key strategy for the Royal Irrigation Department to achieve successful water management involves the proper and timely management of a learning organization in response to changing circumstances. Furthermore, there is an urgent need to enhance the efficiency and effectiveness of leadership, farmer participation, and environmental management to ensure sustainable water management development in the future.